MENGUJI HUKUM LOTKA DALA BIDANG ILMU PERPUSTAKAAN DAN INFORMASI KAJIAN PADA BERKALA PERPUSTAKAAN DAN INFORMASI (BIPI) 2003-2016 - Pergola Irianti (VISI PUSTAKA: Buletin Jaringan Informasi Antar Perpustakaan, 2019)
This study aims to examine Lotka's law relating to the productivity of authors in the field of library and information, especially authors whose works have been published in Berkala Ilmu Perpustakaan dan Informasi (BIPI) in the 2003-2016 period. The quantitative approach of bibliometric analysis using Lotka's law is the method used in this study. The results of data analysis of the first author (straight count) show a maximum deviation of 0.0350 with a critical value of 0.1025. If the maximum deviation is less than the critical value, it indicates that there is conformity of the author's productivity between theory and observation. Similarly, for the inclusion of all authors (complete count), the maximum deviation is 0.0239 with a critical value of 0.0887. Based on these two findings, it can be concluded that Lotka’s law tends to be applied to know the productivity of authors in the field of library and information science.